Designing industrial landscapes for mitigating air pollution with spatially‐explicit techno‐ecological synergy. Issue 10 (18th June 2021) - Charles, Michael; Bakshi, Bhavik R.
Abstract: Air pollution has posed health and environmental threats since the Industrial Revolution. Technological solutions present major expenses for industry, yet nature's ecosystems also provide pollution uptake. In the pursuit of techno‐ecological sustainable design, this work presents a framework for spatially‐explicit industrial site design that determines where and when ecological restoration should be considered. The framework considers land use changes and identifies the cheapest balance between technological and ecological uptake for industrial landscapes, including the impacts of long term ecological growth dynamics. This work presents the framework's construction along with a case study conducted for a coal‐fired power station in Ohio. The results provide spatial maps of proposed restoration areas, projected savings values, and spatial‐temporal maps that consider annual budget constraints. The results demonstrate a significant sensitivity to land use restoration costs and highlights ecological advantages, like simultaneous uptake of different chemical species.